2018
DOI: 10.1177/2053168017753873
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes toward presidential veto powers

Abstract: Previous research on presidential powers has demonstrated predictable variation in the level of support for presidential usage of those powers. However, much of this work has focused solely on unilateral powers. Here, we seek to further explore public attitudes towards constitutionally prescribed powers-namely that of the executive veto. Using original survey data, we find that public support of the president's use of the veto is dependent on respondent partisanship as well as approval of both the president an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…In addition, education has a negative and statistically significant relationship with support for a veto. This differs from Reeves and Rogowski’s () and Sievert and Williamson’s () finding that higher levels of education are associated with higher levels of support for the veto. This makes sense because their question asked respondents to agree or disagree: “The president should not be able to veto legislation that has been passed by both chambers of Congress.” Those with higher levels of education would be more likely to know that the Constitution gives the president this power.…”
Section: Exercise 3: Estimating Veto Support As a Function Of Party Acontrasting
confidence: 97%
See 3 more Smart Citations
“…In addition, education has a negative and statistically significant relationship with support for a veto. This differs from Reeves and Rogowski’s () and Sievert and Williamson’s () finding that higher levels of education are associated with higher levels of support for the veto. This makes sense because their question asked respondents to agree or disagree: “The president should not be able to veto legislation that has been passed by both chambers of Congress.” Those with higher levels of education would be more likely to know that the Constitution gives the president this power.…”
Section: Exercise 3: Estimating Veto Support As a Function Of Party Acontrasting
confidence: 97%
“…The question remains whether this partisan‐conditioned support for a veto changes based on which party holds the presidency. Reeves and Rogowski () and Sievert and Williamson’s () found that Democrats were more likely to favor the president’s ability to use a veto. While their question about the veto directs respondents to think “about the Office of the Presidency—and not any particular president,” a Democrat held the presidency at the time and this could influence Democrats’ higher support.…”
Section: Exercise 3: Estimating Veto Support As a Function Of Party Amentioning
confidence: 98%
See 2 more Smart Citations